2024
DOI: 10.1039/d3ta04894b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of ZIF-9@xGO composites as cooperative electrocatalysts for electro-oxidation of benzyl alcohols coupled with H2 production

Sayantan Chongdar,
Anirban Ghosh,
Rajaram Bal
et al.

Abstract: We report microwave assisted rapid synthesis of ZIF-9 nanocrystals. ZIF-9@xGO composites displayed selective electrocatalytic oxidation of benzyl alcohols (benzoic acid yield 84%, faradaic efficiency 88%) together with high H2 production (273 mmol g−1 h−1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Further, three different metal complex@GO (MC@GO) composite materials were prepared under in situ solvothermal condition by varying the GO wt % (3, 5, and 7), which are termed as BMGO3 , BMGO5 , and BMGO7 , respectively. Moreover, it should be noted that though in situ preparation of MC@GO composite materials is challenging compared to general stirring or ultrasonic processes to make such a kind of electrocatalyst, it has also been observed that the latter developments could not lead to highly integrated systems and often result in leaching of individual components and agglomeration of composite materials during electrochemical experimentation . It is evident that the water stability of metal complexes (MCs) makes a pivotal consideration for their multifarious potential applications as electrocatalysts as classical metal complexes are mostly susceptible to degradation in aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, three different metal complex@GO (MC@GO) composite materials were prepared under in situ solvothermal condition by varying the GO wt % (3, 5, and 7), which are termed as BMGO3 , BMGO5 , and BMGO7 , respectively. Moreover, it should be noted that though in situ preparation of MC@GO composite materials is challenging compared to general stirring or ultrasonic processes to make such a kind of electrocatalyst, it has also been observed that the latter developments could not lead to highly integrated systems and often result in leaching of individual components and agglomeration of composite materials during electrochemical experimentation . It is evident that the water stability of metal complexes (MCs) makes a pivotal consideration for their multifarious potential applications as electrocatalysts as classical metal complexes are mostly susceptible to degradation in aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained GO dispersion was centrifuged 4 times at 10,000 rpm for 15 min to separate the unoxidized graphite flakes. After that, the single-layer exfoliated GO dispersion was purified using a dialysis membrane to remove ionic impurities and dried at room temperature (30 °C). , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve mixed water electrolysis with a high current density at a lower potential, the electrocatalysts were required to be more active for the EBO reaction. In recent years, some electrocatalysts were reported, such as the Co 3 O 4 , NiCo-MOFs, Ni–Co oxides, and Fe–Co oxide heterostructure. , Among them, the Co 3 O 4 nanoneedle arrays, NiCo-MOFs nanosheet arrays, and Ni–Co oxides/NFs exhibit superior EBO activity. Therefore, the reasonable tuning of the composition and structure of electrocatalysts was expected to effectively enhance the EBO performance and facilitate the acquisition of high-value chemicals and electrocatalytic hydrogen production.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic framework (MOF) materials possess a highly adjustable structure, thanks to their secondary structural units composed of organic ligands and metal ions. By controlling the metal ions and ligands, MOFs can exhibit diverse properties, leading to their widespread application in catalysis, separation, and adsorption fields. The unique structural features of MOFs enable them to function as both homogeneous and heterogeneous catalysts. Moreover, their inherent transport pathways and uniform porous structures facilitate high gas accessibility, diffusion, and catalytic activity. , Additionally, the ultrathin structure of MOFs results in a high proportion of exposed active sites on the surface, promoting rapid electron transfer and mass transport due to the presence of many dangling bonds and coordination unsaturated metal sites.…”
Section: Introductionmentioning
confidence: 99%